Uji Efektivitas Larvasida Ekstrak Daun Pegagan (Centella asiatica L. Urban) Terhadap Larva Culex quinquefasciatus - Gina Sonia Rahmah; Khairunnisa Z.; Vera Novalia; M. Khalilul Akbar (Publikasi Indonesia, 2022)
Culex quinquefasciatus is a vector of filariasis (elephantiasis) and Japanese encephalitis. Filariasis is still an unresolved disease in Indonesia. The use of temephos as a chemical larvicide repeatedly causes environmental pollution and is difficult to decompose, so the World Health Organization recommends looking for alternative effects. Gotu kola leaf extract contains metabolic substances such as steroids,saponins, flavonoids, phenolics that can be used as larvicides. This study aimed to determine the effectiveness of the larvicide extract of pegagan (Centella asiatica L. Urban) on the mortality of Culex quinquefasciatus larvae. This study used an experimental research design with a posttest only control group design using 4 concentration groups and 2 control groups, consisting of 4 repetitions in each, namely concentrations of 125 ppm, 250 ppm, 500 ppm, 1000 ppm, abate positive control and aquadest negative control. with the mean larval mortality was 31%, 65%, 81%, 98% which was observed for 48 hours. The number of larval deaths was analyzed using the Kruskall-Wallis test and logit analysis. The results of the analysis showed that pegagan leaf extract had an effect on the mortality of Culex quinquefasciatus larvae with a significant value (p < 0.05), then the results of logit regression analysis showed the LC50 value of 206.71 ppm. The conclusion of this study was that the leaf extract of pegagan (Centella asiatica L. Urban) was effective against the mortality of Culex quinquefasciatus larvae.